Advances in Lipid Metabolism - Valenzuela Baez, Rodrigo (IntechOpen, 2020)
This edited volume is a collection of reviewed and relevant research chapters concerning developments within the field of lipid metabolism. It includes scholarly contributions from experts in the field that cover such topics as roles of lipids in cancer, analytical tools for lipid assessment in biological assays, plant lipid metabolism, the effect of nanoparticles on lipid peroxidation in plants, and fatty acid compositions in fermented fish products. This book provides a thorough overview of the latest research efforts by international authors on lipid metabolism, and opens new possible research paths for further novel developments.